2013
DOI: 10.5836/ijam/2013-04-04
|View full text |Cite
|
Sign up to set email alerts
|

Measuring agricultural sustainability at the farm-level: A pragmatic approach

Abstract: With increasing political pressure to produce more food whilst being environmentally and socially considerate, alongside the need to cope with climatic extremes and financial instability, farming needs to become more sustainable. To monitor and improve understanding of sustainable agriculture, farmers will need additional tools to illustrate the impacts of their business decisions. However, current tools to monitor the sustainability of agriculture require measurement of variables that are rarely readily avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This calls for a new category of indicators which measures the effi ciency of production in relation to both inputs and environmental impact. In recent years there has been a concerted effort to monitor progress towards sustainable intensifi cation (see, for example, Frater and Franks, 2013;Barnes and Thomson, 2014).…”
Section: New Indicatorsmentioning
confidence: 99%
“…This calls for a new category of indicators which measures the effi ciency of production in relation to both inputs and environmental impact. In recent years there has been a concerted effort to monitor progress towards sustainable intensifi cation (see, for example, Frater and Franks, 2013;Barnes and Thomson, 2014).…”
Section: New Indicatorsmentioning
confidence: 99%
“…The Food and Agriculture Organization (FAO) defines sustainable agriculture as "development that meets the needs of current generations without threatening the future generations' ability to meet their needs and aspirations" [6]. However, according to Frater and Franks (2013) [7], sustainable development distributes natural resources spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method used in the evaluation of sustainability is the index method. When the studies carried out to date were examined, it was observed that studies were carried out not only at the farm level (Gameda et al 1997;Rigby et al 2001; Van der Werf & Petit 2001;Frater & Franks 2013;Moore et al 2014;Ryan et al 2014;Waney et al 2014), but also at regional, national and global levels (Trisorio 2004;Gomez Limon Jose & Riesgo 2008;Ceyhan 2010;Vecchione 2010).…”
Section: Introductionmentioning
confidence: 99%